2022
DOI: 10.3389/fonc.2022.815326
|View full text |Cite
|
Sign up to set email alerts
|

NLRC3 High Expression Represents a Novel Predictor for Positive Overall Survival Correlated With CCL5 and CXCL9 in HCC Patients

Abstract: NLRC3 (NLR family caspase recruitment domain containing 3) has been reported as a factor of inhibiting inflammatory responses. It’s role in HCC (hepatocellular carcinoma) is still unknown. In this study we firstly used the GEO (Gene Expression Omnibus) database and mIHC (multiple immunohistochemical analysis) with TMAs (tumor tissue microarrays) of HCC patients to evaluate NLRC3 levels. The tumor-bearing mouse models were also established with NLRC3 over-expressing and knock-down Hepal-6 cells to assess its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous studies have confirmed that NLRC3 prevents colorectal cancer growth by suppressing the PI3K-mTOR signaling pathway and that it may suppress HCC progression by promoting CD8 + T-cell infiltration 7 , 8 . Our study revealed a significant correlation between the expression of NLRC3 and the tumor immune microenvironment of LUAD.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have confirmed that NLRC3 prevents colorectal cancer growth by suppressing the PI3K-mTOR signaling pathway and that it may suppress HCC progression by promoting CD8 + T-cell infiltration 7 , 8 . Our study revealed a significant correlation between the expression of NLRC3 and the tumor immune microenvironment of LUAD.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies have shown that NLRC3 is dysregulated across many cancers and implicated in their progression. For example, NLRC3 prevents colorectal cancer growth by suppressing the PI3K-mTOR signaling pathway and may suppress hepatocellular carcinoma (HCC) progression by promoting CD8 + T-cell infiltration 7 , 8 . However, information available on the expression, regulation, and clinical significance of NLRC3 in LUAD remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the distinct role of CXCL9 remains less clear as experimental studies report direct angiostatic and antifibrotic effects of the CXCL9/CXCR3 under pre-cirrhotic conditions [ 29 ], while elevated CXCL9 serum levels potentially contribute to hepatic as well as extrahepatic organ dysfunction in cirrhotic patients predicting poor overall survival [ 30 ]. In HCC, CXCL9 is associated with the recruitment of tumor-infiltrating immune cells (mainly CD4+ and CD8+ lymphocytes) shaping the TME and possibly amplifying anti-tumor responses of cytotoxic T cells [ 31 ]. Former studies identified different cytokines associated with HCC development in different underlying liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…CTLA4, an immunological checkpoint molecule, can influence the TME of CM by binding to B7 (CD80/CD86) molecules on melanoma antigen-presenting cells to down-regulate T cell activation ( 44 ). The chemokine CXCL9 (C-X-C motif chemokine ligand 9) correlates positively with CD8 + T cell infiltration in solid malignancies ( 45 , 46 ). CXCL9 is abundantly expressed in several solid tumors, including CM, and it stimulates the infiltration of CD4 + T and CD8 + T lymphocytes into tumor cell regions, hence boosting the response of cytotoxic T lymphocytes and destroying tumor cells ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%